الضغوط النفسية وعلاقتها بالاكتئاب لدى أمهات الأطفال ذوي التوحد الطفلي بمدينة الرياض بالمملكة العربية السعودية - الدوسري، هيفاء شبنان بداح (المؤسسة العربية للاستشارات العلمية وتنمية الموارد البشرية, 2022)
هدفت الدراسة إلى فحص العلاقة الارتباطية بين الضغوط النفسية والاكتئاب لدى أمهات الأطفال ذوي اضطراب التوحد الطفلي بالمراكز المتخصصة بالرياض، كما هدفت الدراسة إلى عقد مقارنات بين أفراد عينة الدراسة في كل من الضغوط النفسية والاكتئاب في ضوء متغير الاضطراب النمائي، وذلك بعقد مقارنات بين أفراد عينة الدراسة من الأمهات ذوات الطفال التوحديين وبين أمهات الأطفال الطبيعيين، وقد تكونت عينة الدراسة من (80) أماً لأطفال من ذوي اضطراب التوحد الطفلي، و(80) أماً لأطفال طبيعيين من الجنسين مكافئين لهم في العمر الزمني بالشهور. وتراوحت أعمار الأمهات أفراد عينة الدراسة ما بين 35-42 عاماً. وتبنت الدراسة المنهج الوصفي (الارتباطي/المقارن). وبعد تحليل بيانات الدراسة إحصائياً باستخدام معامل ارتباط بيرسون واختبار "ت"، توصلت الدراسة إلى نتائج تشير إلى ارتباط الضغوط النفسية إيجابياً بالشعور بالاكتئاب لدى أمهات الأطفال ذوي التوحد الطفلي، كما تبين أن أمهات الأطفال ذوي التوحد الطفلي لديهن شعور مرتفع بالضغوط النفسية والاكتئاب أكثر من قريناتهن من أمهات الأطفال الطبيعيين. The study aimed to scrutinize the correlation between psychological stress and depression among mothers of children with infantile autism disorder in specialized centers in Riyadh. The study also aimed to make comparisons between the study sample members in both psychological stress and depression in light of the developmental disorder variable, by making comparisons between the study sample members of mothers with autistic children and mothers of normal children. The study sample consisted of (80) mothers of children with infantile autism disorder, and (80) mothers of normal children of both sexes after they were matched on chronological age socio-economic status. The ages of the mothers in the study sample ranged between 35-42 years. The study adopted the descriptive (correlative/comparative) method. After analyzing the study data statistically using the Pearson correlation coefficient and the "t" test, the results that have been reached indicated that psychological stress is positively related with feelings of depression among mothers of children with infantile autism, and indicated as well that mothers of children with infantile autism have a higher feeling of psychological stress and depression than their peers among mothers of normal children.
Keywords: الضغوط النفسية -- الاكتئاب النفسي -- أمهات ذوي التوحد -- أطفال التوحد -- المجتمع السعودي